Multiple internal resorption in permanent teeth associated with hyperparathyroidism - Eswar Nagaraj; Roopam Pal Kaur; P H Raghuram; P Suresh Kumar (Wolters Kluwer Medknow Publications, 2013)
Internal resorption has been described as a resorptive defect of internal aspect of tooth. It is caused by transformation of normal pulp tissue into granulomatous tissue with giant cells which resorb dentin. Though mostly idiopathic in origin, trauma, caries and restorative procedures have also been suggested to be contributing factors of internal resorption of pulp. Most of the internal resorption cases were found on isolated individual tooth. There are few case reports on multiple root resorptions. External root resorption have been frequently associated with systemic disorders like renal diseases hyperparathyroidism, rickets etc. A rare association of multiple internal resorption of permanent teeth (including lateral incisors, canines, premolars, sparing 2 nd and 3 rd . Permanent molars and missing 35,36, 42) with elevated levels of PTH and uric acid was evident in a 28 year old female patient who presented with fracture of crowns of permanent teeth. Though many cases related to dental manifestations of chronic renal disease and internal resorption of permanent teeth have been documented in literature, there is no evidence on association of hyperparathyroidism with multiple internal resorptions of teeth.